2012
DOI: 10.5588/ijtld.11.0146
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of vitamin D deficiency in Ugandan HIV-infected patients with and without tuberculosis

Abstract: The prevalence of optimal vitamin D status was relatively high in HIV-infected patients with and without TB living near the equator. No difference in 25D concentrations was observed between TB-IRIS and non-IRIS. However, 25D concentrations decreased during ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…1,2,4,5,11,12,14,23,28,30,3237,39,4043,46,47 Our analysis showed that VDD was significantly associated with an increased risk of TB (OR =2.57; 95% CI =[1.74, 3.80]; P <0.00001; I 2 =83) (Figure 2B). Subgroup analysis revealed similar result for the Asian population (OR =2.62; 95% CI =[1.63, 4.23]; P <0.0001; I 2 =71); however, VDD was not associated with an increased risk of TB in the African population (OR =1.89; 95% CI =[0.82, 4.33]; P =0.13; I 2 =91) (Figure 2B).…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…1,2,4,5,11,12,14,23,28,30,3237,39,4043,46,47 Our analysis showed that VDD was significantly associated with an increased risk of TB (OR =2.57; 95% CI =[1.74, 3.80]; P <0.00001; I 2 =83) (Figure 2B). Subgroup analysis revealed similar result for the Asian population (OR =2.62; 95% CI =[1.63, 4.23]; P <0.0001; I 2 =71); however, VDD was not associated with an increased risk of TB in the African population (OR =1.89; 95% CI =[0.82, 4.33]; P =0.13; I 2 =91) (Figure 2B).…”
Section: Resultsmentioning
confidence: 71%
“…1,4,5,11,12,14,22–28,30,3544,46 Our analysis with a random-effect model showed a significantly lower serum/plasma 25(OH)D level in TB patients vs controls (MD =−13.05; 95% CI=[−19.02, −7.08]; P <0.0001; I 2 =96) (Figure 2A). Subgroup analysis showed similar result for the Asian population (MD =−14.64; 95% CI =[−20.15, −9.13]; P <0.00001; I 2 =89); however, there was no such significant difference for the African population (MD =−6.05; 95% CI =[−20.54, −8.43]; P =0.41; I 2 =98) (Figure 2A).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The prevalence of VDD among TB patients in Africa is reported to range from 8.5% to 62.7%. [49505152535456] This discrepancy in the frequency is probably due to the differences in geographical locations of the countries, dietary habits, baseline HIV coinfection, and techniques of vitamin D measurement.…”
Section: Introductionmentioning
confidence: 99%